The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1542/peds.2013-1864
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Youth Seeking Emergency Care for Assault Injuries

Abstract: WHAT'S KNOWN ON THIS SUBJECT:The emergency department (ED) is a critical contact location for youth violence interventions. Information on the characteristics of youth, motivations for fights leading to the injury, as well as previous health service utilization of assault-injured youth seeking care is lacking.WHAT THIS STUDY ADDS: Assault-injured youth are characterized in a systematic sample demonstrating frequent ED use and the need to address substance use and lethal means of force in interventions; context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
94
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(102 citation statements)
references
References 69 publications
6
94
2
Order By: Relevance
“…This finding is concerning in light of current data showing that prior violence is a risk factor for future violence and that retaliatory violence is a key reason for fighting. 42,47,80,81 Indeed, among the assault group, almost half said that the assault-related conflict was not over, and many of these youth noted access to firearms. Although other researchers have developed screening tools for future violence, 32,82 retaliation and firearm access are not usually assessed as part of routine clinical ED care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is concerning in light of current data showing that prior violence is a risk factor for future violence and that retaliatory violence is a key reason for fighting. 42,47,80,81 Indeed, among the assault group, almost half said that the assault-related conflict was not over, and many of these youth noted access to firearms. Although other researchers have developed screening tools for future violence, 32,82 retaliation and firearm access are not usually assessed as part of routine clinical ED care.…”
Section: Discussionmentioning
confidence: 99%
“…Two patient groups who reported any drug use within the past six months on a screening survey 42 were eligible for an ongoing natural history study: 1) Patients aged 14-24 years presenting to the ED for assault-related injuries, and 2) A comparison group of patients presenting for other reasons that was proportionally sampled based on sex and age-group (i.e., 14-17 years, 18-20 years, and 21-24 years) characteristics of the assault-related injury group. The present manuscript reports findings from the initial baseline assessment.…”
Section: Participant Recruitmentmentioning
confidence: 99%
“…Written assent/consent (parental consent if ,18 years old) was obtained. Participants self-administered a computerized screening survey 14 to assess study eligibility, specifically past 6-month drug use (the National Institute on Drug Abuse Alcohol Smoking and Substance Involvement Screening Test [NIDA ASSIST] 25,26 ). The CG was recruited in parallel to limit seasonal/temporal variation, and was systematically enrolled to balance the cohorts by age (ie, 14-17, 18-20, 21-24) and gender.…”
Section: Study Protocolmentioning
confidence: 99%
“…4 Among assault-injured youth seeking urban ED care, almost 25% report having a firearm, with recent violence, attitudes favoring retaliation, and illicit drug use cited as key risk factors for illicit firearm possession. 13 Substance use, which is as high as 55% among assault-injured ED youth, 14 has also been shown to be a key risk factor for a range of high-risk firearm behaviors, including weapon carriage, 15,16 unsafe weapon storage, 16 and firearm-related threats against others. 17 Furthermore, although almost 50% of assaultinjured ED youth have a recent mental health diagnosis (eg, major depressive episode, posttraumatic stress disorder [PTSD]), ,20% have received treatment for that illness, 18 and previous studies have not characterized how a preexisting mental health diagnosis may contribute to future firearm violence risk in this population.…”
mentioning
confidence: 99%
“…This finding is consistent with data that demonstrate adolescents with high risk behaviors are more likely to utilize the ED for care. (12,27,28) Although these studies have identified that adolescents who frequently utilize the ED report higher rates of substance use, dating violence, and mental health problems, we additionally identified an association of STIs and preferential use of the ED for care.The findings from this work should be considered in light of several potential limitations. We used a convenience sampling strategy; patients were approached only when research staff were available.…”
mentioning
confidence: 92%